The Empowering Ecopedagogical Communities and Restructuring Environment-Based Early Childhood Education Curriculum in Coal Mining Regions - Hardiyanti Pratiwi; Ikta Yarliani (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
The Early Childhood Education Curriculum should always be thoughtfully tailored to contextual conditions. For institutions situated in coal mining regions, an environmentally-based curriculum becomes imperative to address the ongoing exploitation of the environment. However, it has come to light that Early Childhood Education institutions in coal mining areas have not aligned their curricula with these contextual considerations. In response to this discrepancy, a Participatory Action Research (PAR) initiative was undertaken by a team of researchers in collaboration with mentor subjects, who are Early Childhood Education teachers in the Hatungun, Binuang, Tapin Selatan, and Salam Babaris Districts. The overarching goal was to rectify this less-than-ideal situation. The series of PAR activities proved to be transformative, leading to the graduation of 38 community members equipped with the ability to design, implement, and evaluate environment-based Early Childhood Education practices. This achievement represents a significant step toward nurturing a generation of educators who can effectively engage with the unique challenges of coal mining regions, fostering sustainable and responsible approaches to education that align with the local environmental context. Ultimately, it paves the way for a more harmonious relationship between early childhood education and the environment, contributing to the broader goal of mitigating environmental exploitation.